2015
DOI: 10.21657/tsd.98686
|View full text |Cite
|
Sign up to set email alerts
|

Fractions of heavy metals in the soil after the application of municipal sewage sludge, peat and furnace ash

Abstract: The aim of the study was to evaluate the effect of the addition of various materials, i.e. municipal sewage sludge, furnace ash and peat, as well as various doses of ash-sludge and ash-peat mixtures, on some physico-chemical properties of the soil: pH, hydrolytic acidity, sorption complex capacity, organic C content, the content of P, K and Mg available forms, total content of heavy metals and their forms soluble in 1 mol · dm-3 HCl solution, and their speciation as well. Municipal sewage sludge and of ashslud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…However, the use of ash and slag in smaller quantities is economically profitable and environmentally safe. Antonkiewicz et al (2014) note that in the variants where ash and slag were used, the content of heavy metals did not exceed the MAC.…”
Section: Discussionmentioning
confidence: 90%
“…However, the use of ash and slag in smaller quantities is economically profitable and environmentally safe. Antonkiewicz et al (2014) note that in the variants where ash and slag were used, the content of heavy metals did not exceed the MAC.…”
Section: Discussionmentioning
confidence: 90%
“…According to Pietrzak and McPhail (2004), in soils not contaminated with Cu, this element occurs mainly in less mobile forms (residual fraction + oxides of Fe and Al), while potentially available Cu constitutes only about 10% of total Cu in the soil profile. Antonkiewicz and Pelka [29] showed that in the uncontaminated silt loam, residual fraction constituted 38% of total Cu. In the soils uncontaminated with Cu, however, Kabala and Singh [24], in the case of sandy soil, found a low percentage of residual fraction in the surface and subsurface layers, which was a result of poor soil sorption capacity of this soil.…”
Section: Concentration and Vertical Distribution Of Cumentioning
confidence: 99%
“…Total concentrations of Cu, Zn, Pb, Ca, Mg, and K were measured by FAAS after digestion with concentrated HClO 4 in the open system with reflux. Total organic carbon (TOC) was determined by dry combustion (Ströhlein CS-MAT 5500) and total nitrogen using the Kjeldahl method.…”
Section: Soil Materialsmentioning
confidence: 99%